Statistical inference of constant-stress partially accelerated life tests under type II generalized hybrid censored data from Burr III distribution - Hassan Amal S.; Alsadat Najwan; Kayid Mohamed; Elgarhy Mohammed; Balogun Oluwafemi Samson; Almetwally Ehab M. (Open Physics)
Accelerated life tests (ALTs) involve subjecting units to more extreme conditions than normal to reduce the duration of testing. These tests, whether fully accelerated or partially accelerated, are crucial in life testing research as they help save both time and money. When results from ALT cannot be extrapolated to normal circumstances, partial ALTs are performed. This study introduces a constant-stress partial ALT, which relies on a generalized Type-II hybrid censoring scheme and assumes that the lifetimes of units under the specified conditions follow the Burr III distribution. The estimates of parameters and accelerated factor of the Burr III distribution are obtained under normal use settings by applying the maximum likelihood and Bayesian techniques. Bayesian estimators are generated using symmetric and asymmetric loss functions through the Monte Carlo Markov Chain approach. Additionally, credible intervals and asymptotic confidence intervals are constructed. Simulation research is carried out using different censoring techniques and sample sizes in order to compare the suggested methodologies. Next, two data sets are analyzed to show the value of the proposed approaches. The study’s conclusion contains a summary of its main conclusions.